Anthropogenic Changes in the Frequency and Severity of European Winter Storms : Mechanisms, Impacts and their Uncertainties : Anthropogene Änderungen in Frequenz und Intensität Europäischer Winterstürme : Mechanismen, Auswirkungen und ihre Unsicherheiten - Pardowitz, Tobias (Freie Universität Berlin, 2015)
Abstract iii Zusammenfassung v 1 Introduction 1 1.1 Objectives of the Thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5 1.2 Outline of the Thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5 2 Projected Changes in European Winter Storm Climate 9 2.1 Introduction and Current State of Research . . . . . . . . . . . . . . . . . 9 2.2 Data and Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11 2.2.1 Reanalysis Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11 2.2.2 Global Climate Model Output . . . . . . . . . . . . . . . . . . . . 11 2.2.3 Wind Field Tracking . . . . . . . . . . . . . . . . . . . . . . . . . . 12 2.2.4 Storm Severity Index . . . . . . . . . . . . . . . . . . . . . . . . . . 13 2.2.5 Extreme Value Analysis . . . . . . . . . . . . . . . . . . . . . . . . 15 2.3 Recent and Future Winter Storm Frequency . . . . . . . . . . . . . . . . . 20 2.3.1 Statistical Uncertainty and Natural Variability . . . . . . . . . . . 24 2.3.2 Scenario Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . 25 2.3.3 Model Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . . 27 2.4 Intensities of Recent and Future Winter Storms . . . . . . . . . . . . . . . 30 2.4.1 Statistical Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . 35 2.4.2 Scenario Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . 36 2.4.3 Model Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . . 37 2.5 Summary and Discussion . . . . . . . . . . . . . . . . . . . . . . . . . . . 41 3 Mechanisms Related to Changes in European Winter Storm Climate 45 3.1 Introduction and Current State of Research . . . . . . . . . . . . . . . . . 45 3.2 Data and Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 47 3.2.1 Reanalysis Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . 47 3.2.2 Global Climate Model Data . . . . . . . . . . . . . . . . . . . . . . 47 3.2.3 Assessment of the North Atlantic Oscillation . . . . . . . . . . . . 48 3.2.4 Eady Growth Rate . . . . . . . . . . . . . . . . . . . . . . . . . . . 49 3.2.5 Hadley Cell Characteristics . . . . . . . . . . . . . . . . . . . . . . 50 3.3 Changes in the North Atlantic Oscillation (NAO) . . . . . . . . . . . . . . 50 3.3.1 The NAO in Historical and Recent Climate . . . . . . . . . . . . . 50 3.3.2 Future Changes in the NAO Strength . . . . . . . . . . . . . . . . 51 3.3.3 Changes in the NAO Shape . . . . . . . . . . . . . . . . . . . . . . 52 3.4 Changes in Baroclinicity . . . . . . . . . . . . . . . . . . . . . . . . . . . . 54 3.4.1 Zonal Mean Eady Growth Rate . . . . . . . . . . . . . . . . . . . . 54 3.4.2 Changes in North Atlantic Eady Growth Rate . . . . . . . . . . . 55 3.4.3 Relation to the NAO . . . . . . . . . . . . . . . . . . . . . . . . . . 56 3.5 NAO Influences on European Winter Storms and their Impacts . . . . . . 57 3.5.1 Dependence of Winter Storm Frequency on the NAO . . . . . . . . 57 3.5.2 Dependence of Storm Damages on the NAO Phase . . . . . . . . . 59 3.6 Tropical Origins of Changes in the North Atlantic Oscillation . . . . . . . 62 3.6.1 Assessment of Hadley Circulation Changes . . . . . . . . . . . . . 62 3.6.2 The Influence of the Hadley Circulation on the NAO . . . . . . . . 64 3.6.3 A Rossby Wave Interpretation of the NAO . . . . . . . . . . . . . 68 3.7 Summary and Discussion . . . . . . . . . . . . . . . . . . . . . . . . . . . 72 4 Estimation of Impacts for Future Winter Storms 77 4.1 Introduction . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 77 4.2 Current State of Research . . . . . . . . . . . . . . . . . . . . . . . . . . . 79 4.3 Data and Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 82 4.3.1 Insurance Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 82 4.3.2 Reanalysis Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . 83 4.3.3 Regional Climate Model Data . . . . . . . . . . . . . . . . . . . . . 83 4.3.4 Wind Field Tracking for High Resolution Model Output . . . . . . 84 4.4 Modeling of Storm Damages . . . . . . . . . . . . . . . . . . . . . . . . . . 85 4.4.1 Basic Loss Model . . . . . . . . . . . . . . . . . . . . . . . . . . . . 85 4.4.2 High-Resolution Refinement of the Storm Loss Model . . . . . . . 86 4.4.3 Optimization of Storm Damage Model . . . . . . . . . . . . . . . . 88 4.5 Uncertainties in Regional Loss Projections . . . . . . . . . . . . . . . . . . 91 4.5.1 Historical Losses . . . . . . . . . . . . . . . . . . . . . . . . . . . . 92 4.5.2 Modeling Losses under Recent Climate Conditions . . . . . . . . . 94 4.5.3 Future Changes in Losses . . . . . . . . . . . . . . . . . . . . . . . 95 4.5.4 Uncertainties on Derived Changes . . . . . . . . . . . . . . . . . . 96 4.6 Assessment of Dynamical Downscaling Uncertainties . . . . . . . . . . . . 99 4.6.1 Ensemble Generation Technique . . . . . . . . . . . . . . . . . . . 100 4.6.2 Comparison of GCM and RCM . . . . . . . . . . . . . . . . . . . . 102 4.6.3 Deriving Uncertainties in Modeled Storm Impacts . . . . . . . . . 104 4.6.4 Implications for Climate Change Assessment . . . . . . . . . . . . 106 4.7 Estimates of Return Values for Loss Intensive Winter Storms . . . . . . . 106 4.7.1 Return Values of Historical Winter Storms . . . . . . . . . . . . . 106 4.7.2 Quantification of Uncertainties . . . . . . . . . . . . . . . . . . . . 110 4.7.3 Derived Climate Change Signal and its Uncertainties . . . . . . . . 117 4.8 Summary and Discussion . . . . . . . . . . . . . . . . . . . . . . . . . . . 119 5 Synthesis 125 Bibliography 131 A Supplementary Material 145 Acknowledgement 153 : The large scale fields of severe winds associated with deep extra tropical cyclones pose severe risks to society and economy by damaging both natural and man-made structures over vast areas. This work addresses anthropogenic changes in the frequency and intensity of European winter storm events, their potential impacts as well as the mechanisms related to such changes. On the basis of global climate projections it is found, that severe wind storms over the North Atlantic are generally decreasing in terms of their frequency, however on a band across the North Atlantic and parts of Europe increased frequency of severe storms is identified in connection with increases in their intensities. Changes are consistently identified amongst multiple model projections and for different scenarios on future greenhouse gas emission. The strength of identified changes is however found to depend on the scenario and particularly on the considered climate model. For central Europe, increases in frequency towards the end of the 21st century are identified under SRES-A1B conditions, ranging between -11% and +44% and an ensemble average of 21%. In terms of intensity, storms affecting central Europe occurring once a year are found to increase in strength by about +30%, with individual models projecting changes between -28% and up to +96%. Considerable robustness of results is found, with 7 out of 8 simulations projecting both increased frequency and intensity of winter storms affecting central Europe. With respect to underlying mechanisms for these changes, the relation to projected changes in the North Atlantic Oscillation (NAO), as well as changing baroclinic conditions of the atmosphere are investigated. It is found that the NAO undergoes fundamental changes with respect to both its phase as well as its shape. Consistent to diagnosed changes in storm frequency, the NAO is found shifting towards a more positive phase with its action centers shifting in north-eastward direction, which is related to more favorable growth conditions for cyclones over eastern parts of the North Atlantic and central Europe. The tropical influence on projected changes in the European storm climate are investigated by addressing the relation between the tropical Hadley circulation and the NAO, with a strong relation being identified between a projected northward expansion of the Hadley cell and changes in the NAO. Results from theoretical considerations, interpreting the NAO as a manifestation of a stationary Rossby wave induced by the overtopping zonal winds above the Rocky Mountains, are found to be well aligned with the projected eastward shift of the NAO action centers. Compared to changes in the European storm climate on large scales, the assessment of trends in storm related losses is associated with much larger uncertainty, which beside the large statistical uncertainty result from multiple uncertainty sources along the modeling chain. To quantify the uncertainty resulting from the dynamical downscaling of general circulation model (GCM) output, a methodology has been developed to generate high-resolution ensembles of potentially hazardous storms identified in GCM output. A large source of uncertainty is related to the modeling of local storm losses on the basis of near-surface wind gust estimates. Deriving storm-loss transfer functions on district level yields the advantage of including local differences in the vulnerability against severe winds, however uncertainties on determined vulnerability parameters are shown to be considerable. Grouping districts into larger regions is found to significantly reduce the involved uncertainty, correspondingly reducing the uncertainty inherent to future loss projections. Besides addressing single sources of uncertainty, a methodology has been developed to derive cumulative uncertainty ranges on estimates of future return levels and return periods within an extreme value analysis framework. Results indicate, that under SRES- A1B conditions, the accumulated German wide losses of a winter storm event occurring once in 5 years increases towards the end of the 21st century by about +30%, with an estimated uncertainty ranging between -5% and +87%. Correspondingly, the return period of a 5 year event is found to decrease to about 4.3 years with an uncertainty range between 3.7 to 5.2 years. Even larger increases in losses and decreases in return periods can be identified for events being even more infrequent, however associated with strongly increasing uncertainties on these estimates. Based on transient regional climate model (RCM) projections, German wide winter storm losses are found to increase by about +14% towards the end of the 21st century under SRES-A1B conditions, with individual RCM signals ranging between -14% and +39%, with 9 out of 12 models projecting increased losses. With respect to regional differences in such trends, north-western parts of Germany are found to be more affected with increases of up to 30% in ensemble average, while south- eastern parts feature only moderate increases in losses by about 5%. : Die zerstörerische Wirkung extremer Winde im Zusammenhang mit intensiven extra-tropischen Zyklonen auf natürliche Ökosysteme und menschliche Strukturen stellt eine ernsthafte Bedrohung für Gesellschaft und Wirtschaft dar. Diese Arbeit untersucht anthropogene Änderungen in der Häufigkeit und Intensität Europäischer Winterstürme, potentielle Auswirkungen sowie Mechanismen welche im Zusammenhang zu diesen Änderungen stehen. Auf Basis globaler Klimaprojektionen findet sich eine generelle Abnahme in der Häufigkeit von Winterstürmen über dem Nordatlantik, wobei es auf einem Band über dem Nord Atlantik und Teilen Europas zu einer Zunahme potentiell schadenrelevanter Sturmsysteme kommt, verbunden mit einer Intensivierung dieser Systeme. Diese Änderungen können dabei in Projektionen mit unterschiedlichen Globalmodellen sowie für verschiedene Szenarien bzgl. zukünftiger Treibhausgasemissionen identifiziert werden, wobei die Stärke der diagnostizierten Änderungen vom untersuchten Szenario und vor allem vom untersuchten Modell abhängt. Für Zentraleuropa kann für das Ende des 21. Jahrhunderts unter SRES-A1B Bedingungen eine Änderung in der Häufigkeit von Sturmereignissen zwischen -11% und +44% festgestellt werden, wobei das Ensemble Mittel eine Zunahme um 21% zeigt. Darüber hinaus finden sich Änderungen in der Intensität einjährig wiederkehrender Winterstürme in Zentraleuropa, welche einer Zunahme um +30% entsprechen, wobei individuelle Modellläufe Änderungen zwischen -28% und +96% projizieren. Die Robustheit der Ergebnisse wird dadurch unterstrichen, dass 7 von 8 Simulationen eine Zunahme in sowohl der Häufigkeit als auch Intensität von Winterstürmen in Zentraleuropa projizieren. Im Hinblick auf zugrundeliegende Mechanismen wird in der Arbeit sowohl die Beziehung zu Änderungen in der Nord Atlantischen Oszillation (NAO), sowie die Änderung in den baroklinen Eigenschaften der Atmosphäre untersucht. Dabei können fundamentale Änderungen der NAO identifiziert werden, sowohl bezüglich ihrer Phase als auch ihrer Form. Konsistent zu den Änderungen in der Sturmhäufigkeit findet sich eine Verschiebung hin zu positiveren Phasen der NAO, wobei sich ihre Aktionszentren in nordöstliche Richtung verschieben, welches mit günstigeren Wachstumsbedingungen für Zyklonen über dem östlichen Nordatlantik und über Europa einhergeht. Ein tropischer Einfluss auf Änderungen im Europäischen Sturmklima wird untersucht, indem eine Beziehung zwischen Eigenschaften der Hadley Zirkulation und der NAO hergestellt wird. Dabei findet sich ein enger Zusammenhang zwischen einer nordwärts Ausdehnung der Hadley Zelle und den projizierten Änderungen der NAO. Theoretische Betrachtungen der NAO als Ausprägung einer stationären Rossby Welle, induziert durch die zonale Anströmung der Rocky Mountains können dabei in Einklang gebracht werden mit der diagnostizierten ostwärts Verschiebung der NAO Aktionszentren. Im Vergleich zu großskaligen Änderungen im Europäischen Sturmklima unterliegt die Abschätzung von Trends in sturminduzierten Schäden deutlich größeren Unsicherheiten, welche neben großen statistischen Unsicherheiten auf eine Reihe von Unsicherheitsquellen in der Modellkette zurückzuführen sind. Um die Unsicherheiten der dynamischen Regionalisierung globaler Klimamodelle (GCM) zu quantifizieren, wurde eine Methodik entwickelt um hochaufgelöste Ensemble Simulationen potentiell schadenrelevanter Sturmereignisse zu generieren. Eine große Unsicherheitsquelle stellt außerdem die Modellierung lokaler Sturmschäden auf Basis bodennaher Winden dar. Sturmschaden-Transferfunktionen können dabei auf Landkreisebene abgeleitet werden, mit dem Vorteil, dass lokale Vulnerabilitäten bzgl. extremer Winde abgebildet werden. Dabei entstehen jedoch große Unsicherheiten auf abgeleitete Modellparameter. Durch Zusammenfassen von Landkreisen zu größeren Regionen können diese signifikant reduziert werden, wodurch eine entsprechende Reduktion der Unsicherheit auf projizierte Schäden erreicht wird. Um die separat quantifizierten Unsicherheitsquellen zu Gesamtunsicherheiten zu integrieren, wurde ein Verfahren entwickelt um die kumulativen Unsicherheitsspannen auf abgeleitete Wiederkehrniveaus und Wiederkehrperioden im Rahmen der Extremwertstatistik zu berechnen. Dabei zeigen die Ergebnisse, dass unter SRES-A1B Bedingungen der Deutschlandweite Schaden von Winterstürmen mit einer Wiederkehrperiode von 5 Jahren um etwa +30% zunimmt, mit einer Unsicherheitsspanne zwischen -5% und +87%. Entsprechend reduzieren sich die Wiederkehrperioden von 5 Jahren auf etwa 4.3 Jahre, mit einer Unsicherheitsspanne zwischen 3.7 und 5.2 Jahren. Für seltenere Ereignisse finden sich sogar stärkere Zunahmen in Schäden und entsprechend Abnahmen in den Wiederkehrperioden, wobei diese Abschätzungen mit deutlich größeren Unsicherheiten behaftet sind. Auf Basis transienter regionaler Klimaprojektionen findet sich eine Zunahme Deutschlandweiter Schäden um +14% zum Ende des 21. Jahrhunderts unter SRES-A1B Bedingungen, wobei die Signale individueller Projektionen zwischen -14% und +39% liegen und 9 von 12 Modellsimulationen eine Zunahme projizieren. Im Hinblick auf regionale Unterschiede in diesem Trend, findet sich eine stärkere Betroffenheit der nordwestlichen Regionen Deutschlands mit einer Zunahme der Sturmschäden um etwa 30% im Ensemble Mittel. Für südwestliche Regionen hingegen finden sich nur moderate Änderungen der Schäden um etwa +5%.